Nigeria: a new dawn? - Sen, A (Oxford Institute for Energy Studies, 2012)
Despite being the largest oil producer in Africa, Nigeria has been in the limelight over the last decade for all the wrong reasons. Beginning in the late 1990s, the cosy relationship between Big Oil and a despotic Nigerian state was challenged by popular, and increasingly militant, pressure from local communities, or more properly from armed youth movements. The shift from non-violent protest to militancy, and ultimately to armed struggle, was in many respects the inevitable result of the Nigerian government’s brutal repression of the Ogoni movement. A decade later, the Niger delta is home to a fully-grown local insurgency. While sporadic episodes of violence and attacks on oil facilities have always proved an inherent feature of the Nigerian oil sector, the problems have escalated dramatically since the election cycle of 2003.